Evolution of ancient hydrothermal fluids theoretically inverted with initial oxygen isotopes of water - Chun-Sheng Wei; Zi-Fu Zhao (Scientific Reports)
Abstract While great successes have been achieved during past decades, oxygen isotopic endmembers of water were implicitly adopted by previous studies for quantifying fossil hydrothermal systems worldwide. Both endmember and evolved oxygen isotopes of meteoric (−11.01±0.43 vs. −3.82±0.01‰, one standard deviation of 1SD) and magmatic water (6.57±0.05 vs. 4.21±0.04‰) are, however, theoretically inverted from hydrothermally altered minerals herein. These waters could evolve through binary mixing under isothermal conditions or interacting with susceptible minerals prior to hydrothermal reequilibration. The studied fossil hydrothermal systems can energetically be alive from less than 12 thousand years (Kyr) to 1 million years (Myr). In the viewpoint of thermodynamics and kinetics, caution should be paid to straightforward quantifying hydrothermal systems with the endmember oxygen isotopes of water. Nevertheless, the complexity and diversity of ancient hydrothermal fluids scientifically and methodologically exemplified at the oxygen isotopic level would be secular scenarios during the geodynamic evolution of the continental lithosphere.